Clinical Stability versus Clinical Failure in Patients with Community-Acquired Pneumonia - Aliberti, Stefano; Blasi, Francesco (Seminars in Respiratory and Critical Care Medicine, 2012)
Once antibiotics have been started in patients with community-acquired pneumonia (CAP), the evaluation of clinical outcomes represents one of the essential steps in patient care. Among CAP patients who improve, recognition of clinical stability should be based on both subjective and objective parameters that are locally available in the everyday clinical practice. Different steps in the management of the pneumonia depend on this early outcome, including the switch from intravenous to oral antibiotics, patients' discharge from the hospital, and outcomes after hospitalization. When deterioration occurs in CAP patients, a “treatment failure” or a “clinical failure” should be identified. It is crucial to understand the etiology of failure so as to develop different measures at both international and local levels to prevent adverse outcomes. Finally, several efforts should be made to define incidence, timing, and risk factors for nonresolving pneumonia that, to date, remains one of the most indeterminate clinical outcomes in patients with CAP.
Keywords: community-acquired pneumonia; outcomes; failure; nonresolving pneumonia; stability